IL-2/Anti-IL-2 Complex Attenuates Inflammation and BBB Disruption in Mice Subjected to Traumatic Brain Injury - Gao, Weiwei; Li, Fei; Zhou, Ziwei; Xu, Xin; Wu, Yingang; Zhou, Shuai; Yin, Dongpei; Sun, Dongdong; Xiong, Jianhua; Jiang, Rongcai; Zhang, Jianning (Frontiers in Neurology, 2017)
Traumatic brain injury (TBI) induces the excessive inflammation and disruption of blood-brain barrier, both of which are partially mediated by the activation of microglia and release of inflammatory cytokines. Previous reports showed that administration of regulatory T cells (Tregs) could suppress inflammation and promote neurological function recovery, and that the IL-2/anti-IL-2 complex(IL-2C) could increase the number of Tregs. Thus, we hypothesized that IL-2C-mediated expansion of Tregs would be beneficial in mice subjected to TBI. In this study, mice received an intraperitoneal injection of IL-2C for 3 consecutive days. We observed that IL-2C dose-dependently increased Tregs without affecting the populations of CD4, CD8, or natural killer cells. IL-2C could improve the neurological recovery and reduce brain edema, tissue loss, neutrophils infiltration and tight junction proteins degradation. Furthermore, this complex could also reduce the expression of CD16/32, IL-1β or TNF-α, and elevate the expression of CD206, arginase 1 or TGF-β. These results suggest that IL-2C could be a potential therapeutic method to alleviate excessive inflammation and maintain blood vessel stability after TBI.